Characteristics and risk factors of severe coronary artery disease in systemic lupus erythematosus: A multicenter, Chinese Rheumatism Date Center database study. (26th July 2022) - Ci, Weiping; Zhao, Jiuliang; Qi, Wanting; Gao, Na; Qian, Junyan; Zhang, Guohua; Wang, Yuhua; Pan, Lili; Li, Mengtao
Abstract: Aim: Systemic lupus erythematosus (SLE) with severe coronary artery disease (CAD) is associated with increased mortality. This study aimed to assess the characteristics and risk factors of severe CAD in SLE. Method: This multicenter, cross‐sectional study enrolled consecutive patients with SLE included in the Chinese Rheumatism Date Center registry. Patients with severe CAD including angiography‐confirmed stenosis ≥50% in the left main, ≥70% in other major coronary arteries, or myocardial infarction were classified into the CAD group. Patients without CAD were classified into the control group. Subgroups were stratified according to age (set as above and below 45 and 50 for men and women, respectively) and gender. Binary logistic regression analysis was performed to determine independent risk factors of severe CAD in SLE. Results: Forty‐three patients had severe CAD from a total of 3744 patients with SLE, 30 of whom were female; 35 belonged to the older age group and 8 belonged to the younger age group. In older patients, independent risk factors included age, 5 major CAD risk factors, SLE Disease Activity Index 2000 (SLEDAI‐2K), hyperuricemia, and corticosteroid exposure. In younger patients, the risk factors were 5 major CAD risk factors and positive antiphospholipid antibody (APL). Male risk factors were age and 5 major CAD risk factors, whereas female risk factors were age, 5 major CAD risk factors, SLEDAI‐2K, and positive APL. Three‐vessel disease was most prevalent in patients with severe CAD. Conclusion: We recommend screening for severe CAD in patients with SLE with age‐ and gender‐stratified risk factors.